2019
DOI: 10.1021/acsomega.9b01799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene and MoS2 Flakes in Industrial Oils to Enhance Lubrication

Abstract: Tribological studies of the 2D nanoadditives such as MoS2 and graphene are mostly performed in base oils such as SN500, SN150, or paraffin. We have focused on their effect in lubrication properties of industrial oils (e.g., axle, transmission, and compressor oils) along with SN500 oil employing a four-ball tester. Two types of graphene powders (GpowA with fewer defects than GpowC), MoS2 powder, and their physical mixtures are chosen as nanoadditives. The tribology performance for 0.05 wt% of additives in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…However, in the presence of MoS 2 –ODA, the coefficient of friction gradually decreased for the initial 10 min and then stabilized with no further changes (Figure b). Over the recent past, MoS 2 in variable shapes, viz ., nanosheets, nanoparticles, and nanovesicles, was demonstrated as an additive to different lube oils such as SN-500 mineral oil, liquid paraffin, and rapeseed oil for enhancement of tribological properties. These dispersions (0.05–2 wt %) reduced the friction between the steel tribo-pair in the range of 15–45% (Table ). Herein, a minute dose of MoS 2 –ODA (0.01 wt %) decreased the friction by 48%, a significantly improved frictional property than the reported performance of MoS 2 . The dangling sulfur atoms at outer layers of MoS 2 showed good affinity with the iron surface and formed a MoS 2 -derived tribo-chemical thin film .…”
Section: Resultsmentioning
confidence: 99%
“…However, in the presence of MoS 2 –ODA, the coefficient of friction gradually decreased for the initial 10 min and then stabilized with no further changes (Figure b). Over the recent past, MoS 2 in variable shapes, viz ., nanosheets, nanoparticles, and nanovesicles, was demonstrated as an additive to different lube oils such as SN-500 mineral oil, liquid paraffin, and rapeseed oil for enhancement of tribological properties. These dispersions (0.05–2 wt %) reduced the friction between the steel tribo-pair in the range of 15–45% (Table ). Herein, a minute dose of MoS 2 –ODA (0.01 wt %) decreased the friction by 48%, a significantly improved frictional property than the reported performance of MoS 2 . The dangling sulfur atoms at outer layers of MoS 2 showed good affinity with the iron surface and formed a MoS 2 -derived tribo-chemical thin film .…”
Section: Resultsmentioning
confidence: 99%
“…Among these wear scars, those of h-BN and WS 2 exhibit a deeper and wider wear region (Figure B,C) than those of graphite and MoS 2 (Figure A,D). For MoS 2 , the abundant active elements such as Mo and S play an important role in reducing the wear and increasing the load capacity. , However, the worn surface of graphite shows smaller wear, which is ascribed to the flexible layered graphite filling the worn grooves by exfoliating off few graphene nanosheets and forming stable transfer films on the worn surface. Therefore, it can be inferred that the relationship between the structural evolution and friction performance can be revealed by studying the materials before and after ball-milling.…”
Section: Resultsmentioning
confidence: 99%
“…The two-dimensional (2D) layered materials as lubricant additives were capable of forming protective films or sliding layers on the contact surface, which were very effective in reducing friction and wear . Lately, the bulk layered materials (e.g., graphite, MoS 2 , WS 2 , and h-BN) have extensively been used as lubrication additives to improve the friction and wear properties of lubricants. , Due to the intrinsically low friction properties of the 2D layered nanosheet structures, they were desirable in many engineering applications, where friction coefficients were reduced to 0.07–0.27. The proposed mechanism of the friction-reducing performance, which has been revealed to be a result of a durable boundary film on the rubbing surfaces to prevent metal-to-metal contact, relied on sliding between the layers because of weak van der Waals forces. Consequently, the structure of 2D layered nanosheets played an intriguing role in the lubrication properties, , thus accounting for an unknown relationship between the structure and friction properties. , …”
Section: Introductionmentioning
confidence: 99%
“…The highest reduction in WSD with the addition of GpowA‐MoS 2 in SN500 oil was 55%, and there was no improvement in WSD reduction with the GpowA–MoS 2 in compressor oil. [ 8 ] Gong et al reported that at room temperature (50 N load) the average wear reduction of 50% was obtained by adding 0.5 wt% MoS 2 /Gr to the pure oil. [ 9 ] Addition of rGO‐MoS 2 at optimum 2.0 wt% with applied load 10 N can reduce the friction to μ ~ 0.2, [ 10 ] and an extremely high reduction of friction by 80% also can be observed with MoS 2 /rGO under applied load of 5 N. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%